Densidade urbana e populacional e seus efeitos multitemporais na cidade de Cascavel/PR - Valmorbida, Leomar (2012)
This work compares the urban growth, between the years of 1995 and 2006, with the population evolution of the demographic censuses, carried through between the years of 2000 and 2010. The delimitation and classification of the urban density, in categories, occurred from interpretation of the satellite images of the Landsat-5 sensor Thematic Mapper . Bands 3, 4 and 5 were used, in false composition color (R5G4B3). The classifications of urban density were defined as: high, average and low density. The demographic data concerning the censuses were extracted from the IBGE census sectors. Both the data from satellite images and census data were indexed in a georreferenced base. The grouping of census sectors leads to the use of samples pertinent to the complaints of taxpayers regarding the urban tax registration, registered and ceded by the Municipality of Cascavel/PR. It was also verified the expansion of urban density ratings in conjunction with population growth and percentage of urban area. It was found that, the greatest population evolution was observed in the class of low urban density. While the middle class urban density got minor population growth and urban expansion. It was also observed that the complaints were present in all urban density classes. Thus, we could relate the percentage of dissatisfactions contained in the classification of low urban density as areas of greater flexibility and expansion activities. This framework has made the data became more easily outdated. The changes in terms of constructions, land divisions, zoning and growth occur with intensity in the peripheries, just by the availability of spaces to be explored. The claims generated by users/contributors distributed by region and specialized in the urban area of Cascavel/PR point to the values attributed to the IPTU, taxes, as garbage collection and public lighting and, mainly, regarding the divergences in the measures of the properties (building, houses), that in some cases are with greater measure in the urban tax registration in relation to the constructed area and this affects the value to be collected for IPTU and taxes.